Nanofluidics : an introduction - Li, Zhigang R., 1958- (Boca Raton : Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T & F Informa, plc, 2019)
This book will cover main topics about the fundamentals and applications of nanofluidics. These would be nanofluidics, how it differs from classic fluid mechanics, as well as describing the methodologies of nanofluidics, including numerical approaches, e.g. molecular dynamics simulation and experimental techniques. Fundamental physics and new phenomena in nanofluidics follows, with numerous applications incorporated. Lastly, challenges and future topics are addressed.This book can be viewed as a starting point for studying nanofluidics. It can also be used as a reference in various areas, including lab-on-a-chip technology, medicine, analytical chemistry, physics and engineering.
Fundamentals of classic fluid mechanics and electroosmosis -- Introduction to nanofluidics -- Molecular dynamics simulation -- Nanofabrication -- Nanoscale capillarity -- Nanoscale simple fluid flows -- External flows -- Nanoscale electrokinetic phenomena.
OCLC-licensed vendor bibliographic record.
Keywords: Nanofluids; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Nanotechnology; SCIENCE / Chemistry / Analytic